EUTHYROID SICK SYNDROME - Rai Purnami, Ni Ketu; Ratna Saraswati, Made; Sustika, I Ketut (journal of internal medicine, 2012)
Subclinical thyroid dysfunction is a common clinical problem for which there are many controversial issues regarding screening, evaluation and management. Subclinical hypothyroidism is defined as an elevated serum TSH level associated with normal total or free T4 and T3 levels. Euthyroid sick syndrome (ESS) identifies abnormalities in thyroid function tests observed in patients with systemic nonthyroidal illnesses (NTIs) and those undergoing surgery or fasting. Abnormalities of thyroid function in NTIs have been classified as 1). Low T3 syndrome, 2). Low T3-low T4 syndrome, 3). High T4 syndrome, and 4). Other abnormalities. The condition is not considered to need treatment because there are no symptoms and the tests go back to normal when the stressful illness has passed. It has been reported a case of euthyroid sick syndrome of a 49 years old woman, whoÕs suffering from sistemic illness of space occupaying lession in thoracal VII-VIII (with histopathologycal findings: metastatic adeno carcinoma). We found low levels of T3 (0.49 nmol/L) and TSH (<0.05 uI/ml), but normal levels of T4 (96.91nmol/L). In severely ill patients, T4 decreases and both T4 and T3 are inversely correlated with mortality rate.
Keywords: severe illness, abnormality thyroid function tests, euthyroid sick syndrome